SOME ASPECTS OF THE POPULATION BIOLOGY OF SEA HARE Aplysia dactylomela RANG, 1828 IN TWO BEACHES FROM CEARÁ STATE, BRAZIL - Bezerra, Luis Ernesto Arruda; Carvalho, Ana Fontenele Urano; Cascon, Helena Matthews; Melo, Vânia Maria Maciel (Arquivos de Ciências do Mar, 2017)
This work describes the population biology of the sea hare, Aplysia dactylomela , at two beaches in Ceará State, Brazil. Their habitats were monthly examined for one-year period, at low tide during daytime and the number, size, spawning and breeding behavior were registered. Feeding habits were determined by observation of seaweed species consumed in the field and by dissecting and examining the gut contents of the sea hares. The results showed that the population density of A. dactylomela in tropical waters from Brazil is much lower than those described for populations of temperate and subtropical regions. This might be explained by the intense sun radiation of tropical regions since the other environmental factors were suitable to their settlement. Despite the low density, A. dactylomela is found throughout the year, with recruitment peaks on February and March. Both population density and animal size were different in the two beaches, what might be due to differences in seaweed abundance and quality, degree of sun exposure and man-caused pollution.